2002
DOI: 10.1097/00004010-200201000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Reorganization and Restructuring Achieved Through Merger

Abstract: This article examines hospital reorganization and restructuring activities following merger for two study periods: 1983-1988 and 1989-1996. In both periods, hospitals rated strengthening hospital financial position as the most important reason for merger. There were also similarities in reorganizing actions, especially reductions in service duplication, consolidation of departments and programs, reductions in medical and support FTEs, and reductions in administrative staffing. Hospital mergers during 1989-1996… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 2 publications
5
45
0
Order By: Relevance
“…This effect may be explained by the internal changes that take place after mergers. Other studies have shown that merging hospitals have a higher degree of internal organizational change compared with stable hospitals [47], and that the main intention of mergers is to trigger such change [48,49]. We assume that any internal changes should be implemented 2 to 3 years into the merger, and this explains the significant effect of mergers in later years.…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be explained by the internal changes that take place after mergers. Other studies have shown that merging hospitals have a higher degree of internal organizational change compared with stable hospitals [47], and that the main intention of mergers is to trigger such change [48,49]. We assume that any internal changes should be implemented 2 to 3 years into the merger, and this explains the significant effect of mergers in later years.…”
Section: Discussionmentioning
confidence: 99%
“…Policies aimed at improving hospitals' financial performance and at enhancing and differentiating their reputation in the marketplace are compatible and do not preclude hospitals from responding to the contingent need of coordination through patient sharing [28,61].…”
Section: Discussionmentioning
confidence: 99%
“…Through collaboration, hospital organizations utilize resources more efficiently, facilitate access to other providers' information and clinical expertise [21], and pursue common goals [22]. The propensity of hospitals to form cooperative agreements with other providers is positively associated with their quality of care [23], operational efficiency [24,25], and financial performance [26][27][28]. Extant research documents numerous outcomes of hospital competition, primarily related to the costs, access, and quality of hospital services [29].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Notably, professional employees, such as registered nurses and physicians, may have few job options outside the hospital sector, at least outside the big cities. Bazzoli et al (2002) suggest that hospital mergers in the USA during both the 80s and 90s were followed by substantial organizational change, and that this was among the main stated reasons for the merger. On the other hand, Fulop et al (2005) argue that in the NHS, which shares more similarities with the Norwegian hospital sector, the context of the public sector with multiple stakeholders, conflicting objectives, and strong professions make a merger process more complex.…”
Section: Theory and Hypotheses Turnover During Mergersmentioning
confidence: 99%